Penerapan Aliran Filsafat Empirisme dalam Manajemen Pembelajaran guna meningkatkan Kompetensi Guru di MAS Al Barakah - Deni Rahmat (Rayah Al-Islam, 2020)
Writing this article aims to expose the governance of education based on the perspective of the experimental empirical philosophy spearheaded by Thomas hobes in MAS Al-Barakah, according to the emphatism, the education was based on experience, as more experience would result in more knowledge. In other words the implication is that truth or knowledge is when a material or concept can be acquired from experience by observing its practical use. The approach to studies used in this article is the study of the literature and observation of experimental empirical philosophy, collecting some existing libraries, data, and news that were later analyzed and thus obtained its essence. The results of the discussion in this article explain that teacher competence at the MAS Al-Barakah education institute is progressing in the field of study of science not only only the learning materials in the classroom but the experience also directed teachers to apply the learning methods acquired with practical and creative concepts, with practice and this experience will be helpful when teachers teach class as well as outside the class.